Characteristic MR findings suggesting presumed labyrinthine hemorrhage. (2nd December 2017) - Kim, Dong Sun; Park, Dong Woo; Kim, Tae Yoon; Lee, Sangjoon; Lee, Young Jun; Lee, Ji Young; Lee, Seung Hwan; Chung, Jae Ho
Abstract: Objectives: To evaluate the magnetic resonance imaging (MRI) findings of labyrinthine hemorrhage as a cause of sudden sensorineural hearing loss (SSNHL). Methods: MRI scans of 59 patients with SSNHL were retrospectively analyzed and compared to clinical features and audiometry data. MR images included pre-enhanced T1-weighted, 3D FLAIR volume isometric turbo spin-echo acquisition (VISTA), post-enhanced T1-weighted and 4-h-delayed enhanced FLAIR VISTA, and 3D thin-section proton density-weighted images. Results: High labyrinth signals were seen on pre-enhanced T1-weighted and 3D FLAIR VISTA images with no enhancement for 6 of 59 (10.2%) patients with SSNHL. In these six patients with presumed inner-ear hemorrhage, high signal intensity was seen in the endolymphatic and perilymphatic portions of the labyrinth on T1-weighted and 3D FLAIR VISTA images. In patients with SSNHL with nonhemorrhagic causes such as vestibular schwannoma or labyrinthitis, high signal or labyrinthine enhancement was seen only in the perilymphatic portion of the labyrinth on pre- or post-enhanced 3D FLAIR VISTA images. Conclusions: MRI using pre-enhanced T1-weighted, 3D FLAIR VISTA, and post-enhanced T1-weighted, 4-h delayed enhanced FLAIR VISTA images is able to identify labyrinthine hemorrhage as the cause of SSNHL. High signals in both the endolymphatic and perilymphatic portions of the labyrinth on pre- or post-enhanced 3D FLAIR VISTA images without enhancement indicate labyrinthine hemorrhage.